Pengaruh Pola Asuh Orang Tua terhadap Prestasi Belajar Mahasiswa PGSD - Pramesti, Amellya Erza Putri; Pinasti, Rachma Indria; Izzuwana, Fadilah; Almawanto, Tiara Azzahra; Widiastuti, Ridahani; Azizah, Istiqomah Astri Nur (Elementary Education Journal, 2023)
Background: Every parent must have a different way of educating and guiding their child. This method is called parenting style. Parenting style in the family means the habits of parents, father or mother in leading, caring for and guiding children in the family. . Method: This research is a type of ex post facto research that aims to determine the effect of parenting parents on student achievement in class 4C PGSD Muhammadiyah University Surakarta. The independent variable in this study is parenting style, while the dependent variable is student achievement. The population of this study were 14 class 4C PGSD students at Muhammadiyah University of Surakarta. The sampling technique is to use random sampling technique. The data from this research were obtained from a questionnaire that can be accessed from Googleform. Result: The results of this study are democratic and permittive parenting styles have a higher value compared to other parenting styles. Implication: The implications of this study are: First, the elementary schools' headmasters in Indonesia should enrich the teachers' knowledge and insight related to parenting style. Second, the government, supported by researchers, has to design an excellent assessment system to solve time limitations. Novelty: The present study revealed the implementation of learning achievment in elementary school comprehensively.